Qualidade fisiológica e bioquímica de cultivares de cebola submetida a concentrações de cloreto de sódio - Corrêa, Natália Silveira (2012)
Salts are prejudicial to growth by toxic effect and osmotic effects, i. e., physiological drought. To some crops as vegetables in general, the problem is more drastic due to great salinity effects. This research had as objective analyze the influence of salt on physiological behavior of onion (Allium cepa L.) seeds. The experiment was realized on two stages, the first determined the effects of several concentrations of sodium chloride (0; 40; 80; 120 and 160 mM NaCl) on seeds physiological quality and seedlings growth in three cultivars (Fepagro 27, Madrugada and Petroline). Tests were conducted using 4 subsamples of 50 seeds for each cultivar, for each treatment, with 3 replications, being evaluated through of the follow tests: germination, first count of germination, germination rate index, emergence, length of shoot and roots, seedlings total dry matter, and electrical conductivity. In general, for all tests applied, the onion seeds showed more sensible when NaCl concentrations were up to 80 mM, indicating that the increase of NaCl diminished the viability and vigor of onion seeds. The second stages the assay was done in order to quantify the chemical composition, comprehending the follow measured: total soluble proteins, total soluble sugars, starch and the determination of -amilase activity. The results indicated that salt concentration affected negatively all variables, decreasing amilase activity, as well as the starch break, consequently the sugar production and restraining the embryo growth.